Information Processing System for Psychophysical Research with Two- and Three-dimensional Presentation of Test Signals - Lazurik, V.T.; Styervoyedov, M.G.; Varlamova, N.V. (Control systems & computers, 2020)
The importance of creating psychodiagnostic equipment, taking into account modern informational capabilities, is considered. The purpose of the work is to develop a conceptual model of an information processing system with the ability to represent two- and three-dimensional test signals, remote control of the testing process, data collection and storage on a remote server. The use of the IoT concept is proposed to create a conceptual model of an information proces-sing system with a remote control function. The structure of an information proces-sing system containing a control unit, a testing unit, an unit for receiving and transmitting data, and an unit for processing and storage data is considered. The components of the testing unit and their interaction with each other and the components of receiving and transmitting data are considered. A description of the devices for 2- and 3- dimensional test signals is given. A model of the device “Cube” for three-dimensional representation of light signals has been created. The structure of the information processing system database has been developed and presented. Мета статті. Об’єктом дослідження є автоматизований процес психофізичної діагностики людини. Мета роботи — розробка концептуальної моделі системи обробки інформації зі здатністю тривимірного представлен-ня тестових сигналів, дистанційним керуванням процесом тестування, збором даних та збереженням їх на від-даленому сервері. Результати. Розглянуто структуру інформаційно-вимірювальної системи, що містить блоки управління, тестування, отримання й передачі даних та блок обробки і збереження даних. Описано компоненти блоку управління. Представлено діаграму класів блоку управління. Розглянуто компоненти блоку тестування та їхня взаємодія між собою та компонентами збору і передачі даних. Наведено опис пристроїв для 2-вимірної та 3-вимірної подачі тестових сигналів. Створено модель пристрою «Куб» для об’ємного подання світлових сигналів. Розроблено та наведено структуру бази даних інформаційно-вимірювальної системи. Цель статьи. Объектом исследования является автоматизированный процесс психофизической диагностики человека. Цель работы — разработка концептуальной модели системы обработки информации со способностью трехмерного представления тестовых сигналов, дистанционным управлением процессом тестирования, сбором данных и хранением их на удаленном сервере. Результаты. Рассмотрена структура информационно-измерительной системы, содержащей блок управления, блок тестирования, блок получения и передачи данных и блок обработки и хранения данных. Описаны компоненты блока управления. Представленная диаграмма классов блока управления. Рассмотрены компоненты блока тестирования и их взаимодействие между собой и компонентами сбора и передачи данных. Приведено описание устройств для 2-мерной и 3-мерной подачи тестовых сигналов.